Effectiveness of interventions to address different types of vulnerabilities in community‐dwelling older adults: An umbrella review - Rhéda Adekpedjou; Pascale Léon; Omar Dewidar; Ali Al‐Zubaidi; Jalila Jbilou; Janusz Kaczorowski; John Muscedere; John Hirdes; George Heckman; Magali Girard; Paul C. Hébert (Campbell Systematic Reviews, 2023)
Abstract Background Frailty, social isolation, loneliness, and poverty may render older adults vulnerable to social or health stressors. It is imperative to identify effective interventions to address them especially in the context of COVID‐19 pandemic. Objective To identify effective community‐based interventions to address frailty, social isolation, loneliness, and poverty among community‐dwelling older adults. Design Umbrella review. Data Source We systematically searched PubMed, Ovid MEDLINE, Embase, Cochrane CENTRAL, EBM‐Reviews, CINAHL via EBSCO, and APA PsycInfo via Ovid from January 2009 to December 2022. Eligibility Criteria We included systematic reviews or quantitative reviews of non‐pharmacologic interventions targeting community‐dwelling older adults. Data Selection, Extraction, and Management Two review authors independently screened the titles and abstracts, performed data extraction and appraised the methodological quality of the reviews. We used a narrative synthesis approach to summarize and interpret the findings. We assessed the methodological quality of the studies using AMSTAR 2.0 tool. Results We identified 27 reviews incorporating 372 unique primary studies that met our inclusion criteria. Ten of the reviews included studies conducted in low‐middle‐income countries. Twelve reviews (46%, 12/26) included interventions that addressed frailty. Seventeen reviews (65%, 17/26) included interventions that addressed either social isolation or loneliness. Eighteen reviews included studies with single component interventions, while 23 reviews included studies with multi‐component interventions. Interventions including protein supplementation combined with physical activity may improve outcomes including frailty status, grip strength, and body weight. Physical activity alone or in combination with diet may prevent frailty. Additionally, physical activity may improve social functioning and interventions using digital technologies may decrease social isolation and loneliness. We did not find any review of interventions addressing poverty among older adults. We also noted that few reviews addressed multiple vulnerabilities within the same study, specifically addressed vulnerability among ethnic and sexual minority groups, or examined interventions that engaged communities and adapted programs to local needs. Conclusion Evidence from reviews support diets, physical activity, and digital technologies to improve frailty, social isolation or loneliness. However, interventions examined were primarily conducted under optimal conditions. There is a need for further interventions in community settings and conducted under real world settings in older adults living with multiple vulnerabilities.